Effect of fuel cell units in economic and environmental dispatch of a Microgrid with penetration of photovoltaic and micro turbine units. (2nd February 2017) - Anastasiadis, Anestis G.; Konstantinopoulos, Stavros A.; Kondylis, Georgios P.; Vokas, Georgios A.; Papageorgas, Panagiotis
Abstract: Recently, Distributed Generation Technologies have gained more attention because of the steady decrease of fossil fuel use and increased load demand. In addition, Microgrid technologies are used to integrate such sources into the main network by drastically improving the utilization of energy via local production and load control. Consequently, improved quality and reliability is achieved. Most studies of such networks focus on operational and investment costs, however neglect the environmental impact. Based on these two criteria, an optimization model is established, in order to determine the viability and the environmental contribution of Microgrid. This model includes high penetration of Fuel Cell units and Renewable Energy Sources. In order to accomplice this, the Harmony Search algorithm was used in order to perform hourly optimizations on a Low Voltage Microgrid. Highlights: Introducing a Fuel Cell along with Microturbines and renewable energy helps in cost and emissions' reduction within a Microgrid. Fuel Cells are more friendly for the environment than Microturbines. The penetration of Fuel Cells has no negative impact on the network.